Genetic Association Study of IL2RA, IFIH1, and CTLA-4 Polymorphisms With Autoimmune Thyroid Diseases and Type 1 Diabetes - Borysewicz-Sańczyk, Hanna; Sawicka, Beata; Wawrusiewicz-Kurylonek, Natalia; Głowińska-Olszewska, Barbara; Kadłubiska, Anna; Gościk, Joanna; Szadkowska, Agnieszka; Łosiewicz, Aleksandra; Młynarski, Wojciech; Kretowski, Adam; Bossowski, Artur (Frontiers in Pediatrics, 2020)
Autoimmune thyroid diseases (AITDs) which include Graves’ disease (GD) and Hashimoto’s thyroiditis (HT) as well as type 1 diabetes (T1D) are common autoimmune disorders in children. Many genes are involved in the modulation of the immune system and their polymorphisms might predispose to autoimmune diseases development. According to the literature genes encoding IL2RA (alpha subunit of Interleukin 2 receptor), IFIH1 (Interferon induced with helicase C domain 1) and CTLA-4 (cytotoxic T cell antigen 4) might be associated with autoimmune diseases pathogenesis. The aim of the study was to assess the association of chosen single nucleotide polymorphisms (SNPs) of IL2RA, IFIH1 and CTLA-4 genes in the group of Polish children with AITDs and in children with T1D. We analysed single nucleotide polymorphisms (SNPs) in the IL2RA region (rs 7093069), IFIH1 region (rs 1990760) and CTLA-4 region (rs 231775) in group of Polish children and adolescents with type 1 diabetes (n = 194) and autoimmune thyroid diseases (GD n =170, HT n = 81) and healthy age and sex matched controls for comparison (n=110). There were significant differences observed between T1D patients and control group in alleles of IL2RA (rs7093069 T > C) and CTLA-4 (rs231775 G > A). In addition, the study revealed T/T genotype at the IL2RA locus (rs7093069) and G/G genotype at the CTLA-4 locus (rs231775) to be statistically significant more frequent in children with T1D. Moreover, genotypes C/T and T/T at the IFIH1 locus (rs1990760) were significantly more frequent in patients with T1D than in controls. We observed no significant differences between AITD patients and a control group in analysed SNPs. In conclusion, we detected that each allele T of rs7093069 SNP at the IL2RA locus and G allele of rs 231775 SNP at the CTLA-4 locus as well as C/T and T/T genotypes of rs1990760 SNP at the IFIH1 locus are predisposing in terms of T1D development. Thereby, we confirmed that IL2RA, IFIH1 and CTLA-4 gene locus have a role in T1D susceptibility. The analysis of selected SNPs revealed no association with AITDs in a group of Polish children and adolescents.